SMART TREES MEDIA TO HELP IMPROVING PUPILS’ COUNTING PROFICIENCY IN A KINDERGARTEN - Mohammad Archi Maulyda; Siti Istiningsih; Vivi Rachmatul Hidayati; Ratih Ayu Apsari; Chuthamar Suwanmani Asian (Jurnal Ilmiah Visi, 2020)
Based on the results of a preliminary study conducted on 20 children, the number of children who got 4 stars was 3 children with a percentage (15%), 3 stars were 4 children with a percentage (20%), 2 stars were 3 children with a percentage (15%), while those who got 1 star were 10 children with a percentage (50%). This shows that there are still many children who have not been able to count from 1-10, which means that many children have not achieved their learning completeness. For this reason, it is necessary to take action so that children's learning completeness can be achieved. The purpose of this study was to see the effectiveness of using smart tree media in improving children's numeracy skills 1-10. The design chosen for this study was the Kemmis and Taggart Classroom Action Research Model with 3 cycles. The data collection techniques used are performance techniques to collect data about students' numeracy skills and observation techniques to collect data about the learning process when each action cycle is carried out. The results of the data analysis showed that after the third cycle was completed, the learning completeness of the children reached 80%, meaning that there were 16 children who achieved learning completeness. The conclusion is that smart tree media can improve numeracy skills 1-10 in group A children at An-Nur Labuapi Kindergarten.Berdasarkan hasil studi pendahuluan yang dilakukan pada 20 anak, 3 anak (15%) mendapat 4 bintang, 4 anak (20%) mendapat 3 bintang, 3 anak (15%) mendapat 2 bintang, dan sisanya 10 anak (50%) mendapatkan 1 bintang. Hal ini menunjukkan masih banyak anak yang belum dapat berhitung dari 1-10, yang berarti banhyak anak yang belum tercapai ketuntasan belajarnya. Untuk itu perlu adanya Tindakan yang dilakukan agar ketuntasan belajar anak dapat tercapai. Tujuan dari penelitian ini adalah melihat efektivitas penggunaan media pohon pintar dalam meningkatkan kecakapan berhitung 1-10 pada anak. Desain yang dipilih untuk penelitian ini adalah Penelitian Tindakan Kelas Model Kemmis dan Taggart dengan 3 siklus. Teknik pengumpulan data yang dipergunakan adalah teknik unjuk kerja untuk mengumpulkan data tentang kemampuan berhitung peserta didik dan teknik observasi untuk mengumpulkan data tentang proses pembelajaran pada saat setiap siklus tindakan dilaksanakan. Hasil analisis data menunjukkan bahwa setelah siklus III selesai dilaksanakan ketuntasan belajar anak mencapai 80%, artinya anak yang mencapai ketuntasan belajar berjumlah 16 anak. Kesimpulannya adalah bahwa media pohon pintar dapat meningkatkan kecakapan berhitung 1-10 pada anak kelompok A TK An-Nur Labuapi.